Pulmonary Aspergilloma (Journal of Medicine, 2009)
Pulmonary aspergilloma is a rare disease, usually presenting as secondary invasion of preexisting lung cavity. When a pre-existing lung cavity is colonized by Aspergillus fumigatus it forms a fungal ball (Pulmonary aspergiloma). Presenting symptoms is usually cough, haemoptysis that may be life threatening. The radiological findings are that of a ball like structure within preexisting lung cavity on plain radiography and computerized tomography of the chest. We report a case of aspergilloma in a 70 year old man with past history of tuberculosis presented with the complaint of occasional cough, respiratory distress and occasional low grade fever for two years. It was diagnosed radiologically and confirmed by fine needle aspiration cytology and treated successfully with oral Itraconazole. Key words: Aspergilloma, Pulmonary tuberculosis, Itraconazole doi: 10.3329/jom.v10i2.2836  J MEDICINE 2009; 10 : 149-151